MODEL PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Siswanto Siswanto (State Islamic Institute of Madura, 2010)
Abstract: Learning of Islamic Education (PAI), as a lesson containing of Islamic teachings and foundations of Islamic life, needs to be pursued through developing models for its teaching that can affect the choices, decisions, and development of the learner's life. Developing PAI model includes: a) dichotomous model; causing dualism in the education system, namely non-religious and religious education. b) mechanism model; viewing life consists of various aspects, and education is seen as an investment and development of a set of values of life, each moves and runs according to its function. c) organism model; viewing the educational activityies as a system consisting of live together and work together in an integrated manner towards a specific goal for establishment of a religious life or inspired life by religious values.